Eosinophilic Endomyocarditis: A Rare Case of Neonatal Mortality - Allison J. Pollock; Stacy L. Hitt; Michael A. Stier; Laura M. Houser (Thieme Medical Publishers, Inc., 2015)
Abstract Background Eosinophilic endomyocarditis (EEM) is a rare diagnosis that is extremely uncommon in newborns. This case report aimed to present a case of neonatal mortality from acute cardiac failure due to EEM. Case Our report presents a term male neonate with minor complications in the immediate postnatal course, who was discharged at 48 hours of life, but who developed unexpected respiratory distress, followed by cardiac arrest and death at 3 days of life. One day after discharge, the infant developed respiratory distress and cool skin, and then developed cardiac arrest at the pediatrician's office, undergoing resuscitation with intravenous fluid, cardiopulmonary resuscitation, epinephrine, atropine, and failed intubation. Autopsy revealed EEM, an inflammatory infiltrative process involving the endomyocardium. Pathology Pathogenesis involves three stages: (1) myocarditis with an acute eosinophilic inflammatory infiltrate followed by (2) myocyte necrosis and eventually (3) fibrosis in the final stage of the disease. Discussion The cause of death was acute cardiac failure due to intense eosinophilic infiltration and degranulation with early subendocardial myocyte necrosis but before development of extensive myocyte necrosis. This case appears to be the youngest patient reported with EEM.